2021
DOI: 10.5539/gjhs.v13n5p44
|View full text |Cite
|
Sign up to set email alerts
|

Self-Ear Cleaning Practices and the Associated Risks: A Systematic Review

Abstract: BACKGROUND: Naturally the ear produces soft wax from the sebaceous and ceruminous gland. This is what is referred to as earwax. This wax is important for protection of the ear by trapping dust and other foreign particles that could damage the eardrum. It also has some antibacterial properties. Jaw movements, like during chewing, moves the old earwax from inside the ear canal to the outside and finally flakes off. Build-up of this wax in the ear causes hearing loss, pain in the ear, irritation, dizziness and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…High prevalence was also noted in studies conducted in Saudi Arabia (75%) [12], Nigeria (80%) [6], Malaysia (92%) [13] and Bhutan (92.15%) [14]. Healthcare workers also did not have adequate knowledge and most of them perform matching practice [15,16]. It is as high as 94% in a study by Oladeji et al that was conducted on health workers in a tertiary hospital, which raised concerns considering their role in public awareness [1].…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence was also noted in studies conducted in Saudi Arabia (75%) [12], Nigeria (80%) [6], Malaysia (92%) [13] and Bhutan (92.15%) [14]. Healthcare workers also did not have adequate knowledge and most of them perform matching practice [15,16]. It is as high as 94% in a study by Oladeji et al that was conducted on health workers in a tertiary hospital, which raised concerns considering their role in public awareness [1].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, the innate self-cleaning mechanism of the ear engenders the entrapment and subsequent expulsion of particulate matter, including dust and dirt, along a medial to lateral axis within the ear canal. This process is facilitated by the combined actions of epithelial migration and movements of the jaw 5,6 .…”
Section: Introduction and Purposementioning
confidence: 99%
“…The attitude, awareness and knowledge of the public regarding health hazards and complications of self-ear cleaning are very poor, as there is a common belief that it is beneficial (Afolabi et al, 2009). Many studies have reported poor knowledge regarding self-ear cleaning worldwide (Alateeq et al, 2018;Ghauth et al, 2018;Lukolo et al, 2021;Olajide et al, 2019;Tobih et al, 2021). A study conducted in the Makkah region on a young population demonstrated that 80% of participants had poor knowledge and 60% of them would not consult a doctor if they experienced hearing difficulties (Haji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%